Sources of Parenting Stress Raising Children with Autism Spectrum Disorder: Subjective Experiences of Parents - Alifanovienė, Daiva; Šapelytė, Odeta (Social Welfare: Interdisciplinary Approach, 2025)
Autism is a complex state of the individual’s development manifesting itself in various different forms of behaviour, emotions, communication, etc. which create preconditions for the expression of different experiences. The article aims to reveal the subjective experiences of parents raising children with the autism spectrum disorder (hereinafter ASD) which are related to the sources of parenting stress they experience. A qualitative research approach was chosen to reveal the experiences of the subjects. The data were collected through a semi-structured interview, during which, open-ended questions were used so that not to limit the possible answers according to the assessment domains provided by the researchers. Qualitative content analysis using an open coding procedure was chosen for the analysis of the research data. By reconstructing the multi-layered context of social, cultural, and educational diversity of families raising children with ASD and analysing the subjective experiences of parents, the sources of the stress they experience are revealed. The study highlighted parents’ internal-personal (parents’ internal experiences) and external-social difficulties in relationship with society due to the personality and behavioural characteristics of children with ASD. The latter can be divided into micro (child’s behaviour as a source of stress, challenges encountered in the child’s daily life and changes in the environment) and meso (material challenges, negative societal attitude) spaces.
Keywords: sources of parenting stress; parenting stress; children with autism spectrum disorder (ASD); subjective experiences of parents